PERBANDINGAN DETEKSI OOKISTA Cryptosporidium sp. PADA SAMPEL TINJA DENGAN METODE PEWARNAAN MODIFIKASI TAHAN ASAM DAN AURAMIN FENOL - admin (JURNAL ILMU KESEHATAN BHAKTI SETYA MEDIKA, 2016)
Cryptosporidium sp. is intestinal protozoa parasite intracellular which infect widely vertebrata include human and cause cryptosporidiosis disease, also opportunistic agent for diarrhea. Reinfection and high transmission can decrease quality of life patient, so it needs a quick diagnostic with microscopy analysis to stain fecal smears. The objective of this study is to investigate the comparison of the modified acid fast (MAF) and auramine phenol (APh) staining method in order to detecting Cryptosporidium sp. oocysts from concentrated fecal sample with Water-Eter method. The sensitivity and specificity of each method from concentrated fecal sample was determined with PCR* as the gold standard. The result of the screening test and the levels of agreement were quantified. This research is qualitative interpretation with cross sectional design study which using diagnostic test. Of the 130 fecal samples that has examined, 10%, 19,2% and 32,3% were positive Cryptosporidium sp. by the MAF, APh and PCR* method respectively. The majority of positive Cryptosporidium sp. samples were found in stain fecal smears with APh method. The results have a significant differences (p=0,00) between MAF and APh method to PCR, with kappa score = 0,378 and 0,587. In comparison with PCR* results, the sensitivities of MAF and APh methods were 30,9% and 54,8%; the specificities were 100% and 97,7% respectively. The APh staining method apparently has more sensitivity than MAF staining method, but has the same specificity. The APh staining method proved to be a valuable alternative to MAF staining for detection of Cryptosporidium sp. oocysts in fecal sample.